Hubungan Motivasi Pasien dengan Kepatuhan dalam Menjalani Hemodialisa pada Pasien Gagal Ginjal Kronik di RSI PKU Muhamadiyah Pekajangan Pekalongan - Shisca Octavia Maharani, Shisca Octavia Maharani; Dwi Retnaningsih; Dwi Nur Aini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Chronic Kidney Disease (CKD) is a medical condition that requires renal replacement therapy such as hemodialysis. Patient compliance with this therapy is essential to prevent complications and maintain quality of life. Patient motivation, both intrinsic and extrinsic, plays a significant role in determining the level of compliance. This study aims to examine the relationship between patient motivation and compliance with hemodialysis treatment in CKD patients at RSI PKU Muhammadiyah Pekajangan Pekalongan. This research uses a quantitative correlational design with purposive sampling, involving 67 respondents from a population of CKD patients undergoing hemodialysis, with an average of 80 patients per month. The instruments used were patient motivation questionnaires and hemodialysis compliance questionnaires. The results showed that most respondents had good motivation (74.6%) and positive compliance (76.1%). Bivariate analysis using the Spearman Rank test revealed a significant relationship between motivation and compliance (p = 0.000) with a strong correlation (r = 0.685). This study suggests nursing interventions that focus on enhancing patient motivation to support long-term therapy success. The limitations of this study include the cross-sectional design, which cannot prove causal relationships, and the potential social bias in the self-report instruments.